(untitled) (Research, Society and Development, 2022)
The present literature review sought to identify how the pathophysiology of Type 2 Diabetes Mellitus impacts the intestinal microbiota, as well as the metabolic aspects of the intestinal microbiota may be associated with Type 2 Diabetes Mellitus, in addition to the usual and developing managements. For this, searches were carried out in databases to identify tests in human and animal models, where 28 studies were used for the development of this review. The studies used suggest that the intestinal microbiota of patients with type 2 diabetes mellitus has a role in the pathogenesis and progression of the disease, as well as the disease has an impact on the microbiota of the patient. Regarding management, the usability of drugs is directly associated with the pathogenesis and progression of the disease, without taking into account intestinal dysbiosis, whereas the usability of non-drugs is managed taking into account the pathogenesis and progression of the disease, associated pathways and microbiota. The use of prebiotics, probiotics and symbiotics is still in the development phase, and there is no consensus on how they can impact the disease and the intestinal microbiota of the carrier, nor what dosage can be indicated for management. Finally, more studies are needed, especially in humans, that can direct the usability of prebiotics, probiotics and symbiotics, both in the type of strain and in their dosage, taking into account factors such as age, sex and race.